2010
DOI: 10.1007/s00268-010-0681-3
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Value of Tumor Proliferative Indices in Periampullary Cancers: Ki‐67, Mitotic Activity Index (MI) and Volume Corrected Mitotic Index (M/V) Using Tissue Microarrays

Abstract: In periampullary cancers, Ki-67 and MI are proliferative indices predictive of tumor behavior. M/V was predictive of survival in tumors of the pancreaticobiliary subtype.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 43 publications
1
4
0
Order By: Relevance
“…Additionally, in iCCA, we performed a correlation analysis between the syndecan-1 H-score and the residual tumor classification, the lymph node status, the iCCA subclassification (small and large duct type), and the Ki-67 proliferation rate. As expected, the proliferation rate correlated with histological tumor grade [23]. No statistically significant association between the H-score and the prognostically important marker proliferation rate, residual tumor status, lymph node status, and histological subtype analysis was detected (Ki-67: ρ = 0.08 (p = 0.925), R-status: ρ = 0.062 (p = 0.484), iCCA subclassification ρ = 0.002 (p = 0.985).…”
Section: Discussionsupporting
confidence: 81%
“…Additionally, in iCCA, we performed a correlation analysis between the syndecan-1 H-score and the residual tumor classification, the lymph node status, the iCCA subclassification (small and large duct type), and the Ki-67 proliferation rate. As expected, the proliferation rate correlated with histological tumor grade [23]. No statistically significant association between the H-score and the prognostically important marker proliferation rate, residual tumor status, lymph node status, and histological subtype analysis was detected (Ki-67: ρ = 0.08 (p = 0.925), R-status: ρ = 0.062 (p = 0.484), iCCA subclassification ρ = 0.002 (p = 0.985).…”
Section: Discussionsupporting
confidence: 81%
“…One study has shown that lower levels of Ki-67 were associated with a better outcome in pancreatic cancer patients (37), although other studies did not find an association (38,39). The predictive value of Ki-67 was reinforced by recent studies that showed better survival or decreased tumor volume with lower levels of Ki-67 (40,41). We further confirmed the anti-proliferative effect of PEITC by PCNA staining which has been reported to correlate positively with the histological grade of pancreatic cancer (42).…”
Section: Discussionmentioning
confidence: 98%
“…The proportion of tumour and stroma was estimated visually by both researchers independently. From these figures, the densities of lymphocytes per mm 2 were calculated using the TMA core area as reference [20]. The mean area of TMA cores was 0.355 mm 2 .…”
Section: Methodsmentioning
confidence: 99%